2019
DOI: 10.1007/s40314-019-0991-5
|View full text |Cite
|
Sign up to set email alerts
|

An Augmented Lagrangian algorithm for nonlinear semidefinite programming applied to the covering problem

Abstract: In this work, we present an Augmented Lagrangian algorithm for nonlinear semidefinite problems (NLSDPs), which is a natural extension of its consolidated counterpart in nonlinear programming. This method works with two levels of constraints; one that is penalized and other that is kept within the subproblems. This is done to allow exploiting the subproblem structure while solving it. The global convergence theory is based on recent results regarding approximate Karush-Kuhn-Tucker optimality conditions for NLSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In this section, we prove that the second-order derivatives of G, as defined in (2), are given by (5,7,8,9,10). In [6] we have built appropriate bi-Lipschitz mappings T t in order to use integration by substitution for the differentiation of G(x + tδx, r) and G(x, r + tδr).…”
Section: The Shape Optimization Problemmentioning
confidence: 97%
See 3 more Smart Citations
“…In this section, we prove that the second-order derivatives of G, as defined in (2), are given by (5,7,8,9,10). In [6] we have built appropriate bi-Lipschitz mappings T t in order to use integration by substitution for the differentiation of G(x + tδx, r) and G(x, r + tδr).…”
Section: The Shape Optimization Problemmentioning
confidence: 97%
“…From the practical point of view, underlying partitions that lead to exact calculations might be implemented using power diagrams [4,21]. We observe that formulae (5,7,8,9,10) are valid for general sets A satisfying Assumptions 1 and 2, but the exact numerical computation of G, ∇G and ∇ 2 G requires A to be a union of non-overlapping convex polygons. The exact calculation of ∇G and ∇ 2 G can actually be performed for any set A such that the intersections of ∂A with circles can be computed analytically.…”
Section: Final Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For NLPs it has been shown that this variant possesses strong convergence properties even under very mild assumptions [4,6]. It has since been applied to solve various other problems, including MPCC [7,26], quasi-variational inequalities [27], generalized Nash equilibrium problems [16,29], and semidefinite programming [8,14].…”
Section: Introductionmentioning
confidence: 99%